Neurological Infection, Kynurenine Pathway, and Parasitic Infection by Neospora caninum - Del’Arco, Ana Elisa; Argolo, Deivison Silva; Guillemin, Gilles; Costa, Maria de Fátima Dias; Costa, Silvia Lima; Pinheiro, Alexandre Moraes (Frontiers in Immunology, 2022)
Neuroinflammation is one of the most frequently studied topics of neurosciences as it is a common feature in almost all neurological disorders. Although the primary function of neuroinflammation is to protect the nervous system from an insult, the complex and sequential response of activated glial cells can lead to neurological damage. Depending on the type of insults and the time post-insult, the inflammatory response can be neuroprotective, neurotoxic or, depending on the glial cell types, both. There are multiple pathways activated and many bioactive intermediates released during neuroinflammation. One of the most common one is the kynurenine pathway, catabolizing tryptophan, which is involved in immune regulation, neuroprotection, and neurotoxicity. Different models have been used to study the kynurenine pathway metabolites to understand their involvements in the development and maintenance of the inflammatory processes triggered by infections. Among them, the parasitic infection, Neospora caninum could be used as a relevant model to study the role of the kynurenine pathway in the neuroinflammatory response, and the subset of cells involved.